Characteristics and classification of the peat at Toba Highland, North Sumatera, Indonesia - Sarifuddin, Sarifuddin; Sitohang, Ester Juliana; Mukhlis, Mukhlis (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Peatland serves as a crucial natural resource with hydrological and other environmental functions essential for all living organisms. In some regions, peat soil isn't limited to lowland areas, it is also found in highland areas. This study is a survey research aiming to examine the characteristics of the highland peatlands of Toba North Sumatera, namely in the Village of Matiti II, Humbang Hasundutan Regency, North Sumatera and lowland peatlands as control of peatlands in general in Sidomulyo Village, Bilah Hilir Subdistrict, Labuhan Batu. The study employed a survey research approach with a descriptive method to determine the differences in the characteristics of highland Toba peat soils. In each area, a representative profile was made, and the soil morphology, characteristics and classification were observed according to the 2014 soil taxonomic classification. Soil samples were taken from each layer in the soil profile for soil analysis in the laboratory. Soil analysis included bulk density, pH H₂O, pH NaF, CEC, base saturation, organic C, total N, C/N, electrical conductivity (EC) and ash content. The results showed that the difference in altitude directly affected the microclimate and the hydrologic conditions, which in turn affected the characteristics of the peat soil. In the context of the Toba highland, the main source of peat soils comes from rainfall. In contrast with the peatland of the lowlands, where the impact of tides is a significant factor, the peat of the Toba highland is affected by the surrounding hills.